Research Leadership of the “Priority 2030” Program: Success Factors - A. I. Guseva; V. M. Kalashnik; V. I. Kaminsky; S. V. Kireev (Высшее образование в России)
The article presents the results of comparative analysis of universities’ activities over the past five years, which won the special grant in the “Research Leadership” track of the “Priority 2030” program. The comparison is carried out between the following groups of universities: 1) all universities of the “Research Leadership” track, 2) the first, second and third groups, selected according to the results of the competition, and 3) group of Project 5-100 participants. The state strategic initiatives in the field of the higher education system over the past 15 years were considered to determine their impact on the development of the considered groups of universities; the indicators that make significant contribution to the results of educational, research, international and financial activities of universities were selected. The aggregation of indicators for university groups has been carried out using the Displaced Ideal method and the comparative analysis for 2016 – 2020. The significant indicators of scientific and research activities of analyzed groups of universities for 2018 – 2020 were considered. Based on the analysis, the most significant factors of success have been identified that ensured the victory of the considered universities in the Priority 2030 competition on the “Research Leadership” track.